Effectiveness of Cervical Spinal Cord Stimulation for the Management of Chronic Pain. Issue 3 (24th September 2013) - Deer, Timothy R.; Skaribas, Ioannis M.; Haider, Nameer; Salmon, John; Kim, Chong; Nelson, Christopher; Tracy, Jerry; Espinet, Anthony; Lininger, Todd E.; Tiso, Robert; Archacki, Melinda A.; Washburn, Stephanie N.
<x xml:space="preserve">Abstract</x> Introduction Scientific evidence supports spinal cord stimulation (SCS) as a cost‐effective treatment option that, for many disease states, should be employed earlier in the treatment continuum. Reimbursement for SCS in the cervical spine has recently been challenged based on supposed lack of clinical literature. To refute this assumption, we analyzed data from an international registry to support the use of cervical SCS. Materials And Methods The following outcomes were collected as part of an institutional review board‐approved, prospective, multicenter, international registry: pain relief, Pain Disability Index (PDI) score, quality of life (QoL), and satisfaction at 3, 6, and 12 months post‐implantation. Descriptive statistics are provided for all measures. Changes from baseline in PDI scores were analyzed using Tukey's pairwise comparisons. Results Thirty‐eight patients underwent implantation of SCS leads in the cervical spine at 16 study sites in the United States and 3 international study sites. Direct patient report of percentage of pain relief was 54.2%, 60.2%, and 66.8% at 3, 6, and 12 months post‐implantation, respectively. Pain relief was categorized as excellent/good by 61.6% of patients at 3 months, with similar results observed at 6 and 12 months. PDI scores were significantly reduced at all time points. At 3 months post‐implantation, 92.4% of patients indicated they were very satisfied/satisfied with the SCS device. No patients indicated that they were dissatisfied. Overall QoL was reported as improved/greatly improved by 73.1% of patients at 3 months. Similar results for QoL and satisfaction were reported at 6 and 12 months. Conclusion The results suggest that the use of SCS in the cervical spine is a medically effective method of pain management that satisfies and improves the QoL of most patients. The use of SCS can reduce the high cost of direct medical treatment of pain, as well as increasing the productivity of patients, and therefore should be reimbursed in appropriately selected patients.